2009
DOI: 10.1177/0022343308098405
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Shame: International Organizations and Foreign Aid in the Punishing of Human Rights Violators

Abstract: Are violators of international human rights norms punished with lower levels of foreign aid? Despite their abstract preferences, governments often lack the incentive to punish norm violators bilaterally. Multilateral lending institutions, such as the World Bank, could fill the void if they wanted to consider human rights abuses and could bypass restrictions on evaluating the political character of recipients. This article argues that `shaming' in the United Nations Commission on Human Rights, through resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
141
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(147 citation statements)
references
References 54 publications
5
141
0
1
Order By: Relevance
“…Emilie Hafner-Burton argues that human rights don't just improve on their own accord; improvements are instead associated with hard-nosed efforts by the international community to link preferential trade agreements to improvements (Hafner-Burton 2005). More recently, James Lebovic and Erik Voeten have shown that the World Bank tends to reduce its aid to countries that have been named as severe rights abusers by resolutions of the United Nations Human Rights Commission (now Council) (Lebovic & Voeten 2009). But what no one has shown is that there is any significant external enforcement behind the provisions of international human rights treaties, of a kind that might plausibly account for the patterns of compliance observed across a number of rights areas.…”
Section: Burton and Tsutsui 2005)mentioning
confidence: 99%
“…Emilie Hafner-Burton argues that human rights don't just improve on their own accord; improvements are instead associated with hard-nosed efforts by the international community to link preferential trade agreements to improvements (Hafner-Burton 2005). More recently, James Lebovic and Erik Voeten have shown that the World Bank tends to reduce its aid to countries that have been named as severe rights abusers by resolutions of the United Nations Human Rights Commission (now Council) (Lebovic & Voeten 2009). But what no one has shown is that there is any significant external enforcement behind the provisions of international human rights treaties, of a kind that might plausibly account for the patterns of compliance observed across a number of rights areas.…”
Section: Burton and Tsutsui 2005)mentioning
confidence: 99%
“…Some argue that donor governments prioritize geostrategic or economic considerations over human rights, making it unlikely that aid officials will systematically punish recipient governments for human rights violations (Alesina and Dollar, 2000;Neumayer, 2003a,b). Others find that donor governments sanction human rights violations with reductions in foreign aid, although cuts are limited to specific aid types and sectors (Cingranelli and Pasquarello, 1985;Lebovic and Voeten, 2009;Nielsen, 2013). 2 This paper strengthens our knowledge on the link between human rights and foreign aid policy by developing and testing a model of foreign aid delivery that identifies human rights international non-governmental organizations (INGOs) as an influential force in foreign aid decision making.…”
Section: Introductionmentioning
confidence: 65%
“…Lebovic and Voeten (2009) find that donor governments pressure international organizations to sanction repressive behavior with cuts in multilateral aid, while bilateral aid flows between donors and the repressive recipient government remain unchanged. Nielsen (2013) disaggregates bilateral aid into its various sectors, showing that human rights violations lead donor governments to cut economic aid but not humanitarian aid.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The main exception are autocratic states: those that have better human rights records get more aid than those with bad records. Lebovic and Voeten (2009) test the hypothesis that a developing country that has been criticized in a resolution by the United Nations Commission on Human Rights (UNCHR), will receive less aid. These authors find that such countries do indeed get significant lower World Bank and multilateral loan commitments, but that bilateral aid allocations are not affected.…”
Section: Spatial Spilloversmentioning
confidence: 99%